Active thermal mass enhancement using phase change materials - Whiffen, T.R.; Russell-Smith, G.; Riffat, Saffa (Elsevier, 2016)
Buildings account for around 40% of energy consumption in the UK. For over twenty years active thermal mass systems have been a feature in low-energy buildings in northern Europe. By passing ventilation air, and utilising night ventilation, through the hollow core structures efficient heating and cooling has been achieved. Despite the success, such systems suffer from space overheating and efficiency losses during extended hot periods. Control strategies have largely mitigated this effect however low cost retrofit solutions that enhance the system are of interest. This research therefore investigates the benefit of using innovative phase change material (PCM) solutions to enhance thermal comfort and reduced energy usage of traditional active thermal mass systems.